An international multicenter retrospective analysis of repeated anti-ENA testing in ANA-associated rheumatic diseases, a data-driven proposal to increase testing efficacy - Wim H.M. Vroemen; Maria Infantino; Mariangela Manfredi; Joyce J.B.C. van Beers; Carolien Bonroy; Jan G.M.C. Damoiseaux (Journal of Translational Autoimmunity)
Background: Autoantibodies detection in ANA-associated rheumatic diseases (AARD) is not only used for diagnostic and classification purposes, but also for monitoring. In case of AARD it is questioned if repeated anti-ENA testing is of any substantial value. In this international multicenter retrospective study, repeated anti-ENA testing according to local AARD testing algorithms was investigated. Methods: Anti-ENA results (anti-SSA60, -Ro52, -SSB, -Scl-70, -CENP-B, -RNP, -Sm) over a 6 to 10-year period were extracted from the laboratory information systems of three participating centers. Time between repeated testing was determined and concordance analysis was performed. Results: The study included 28557 anti-ENA requests from 19388 patients (72 % female). In 15227 patients (78.5 %) only one anti-ENA test was performed (79.9 % negative), while 4161 patients (21.5 %) underwent multiple (median [interquartile range (IQR)]; 2 [2–4]) tests with a maximum of 31 tests. The median [IQR] time interval between anti-ENA testing for the total cohort was 364 [195–539] days. Concordance analysis demonstrated that repeated anti-ENA test results did not show any change in 3583 patients (86.1 %). Additional autoantibodies were observed in 243 patients (5.8 %). In 76 (1.8 %) patients a positive anti-ENA test was obtained after an initial negative anti-ENA test result, while in 167 (4.0 %) patients additional autoantibodies were detected after an initial positive anti-ENA result. Conclusions: Repeated anti-ENA testing with a median time interval of about one year is common independently of local laboratory testing algorithms, but showed a limited added value since only 1.8 % of the patients have demonstrated a positive anti-ENA test after an initial negative anti-ENA test. These data at least suggest that repeated anti-ENA tests should be discouraged and only be instigated by a change in clinical manifestations.